The Portuguese publisher Livros do Brasil and its erotic works during the Brazilian military dictatorship - Sandra Reimao (Signo, 2018)
There are five opinions in the Brazilian National Archives, dated 1977, Censorship Service, an organ of the Ministry of Justice, indicating the veto of five erotic books published by the Portuguese publisher Livros do Brasil. Aiming at elaborating a contextualized understanding of these opinions, this study addresses the history of the publisher Livros do Brasil and its editorial profile; and tries to characterize the erotic editions of this publisher that have been banned in Brazil. Finally, it discusses and analyses the specificities of Brazilian censorship opinions and their argumentative articulations.